Makna Adverbia Zenbu Dan Minna Dalam Bahasa Jepang - Sri Wahyu Istana Trahutami; Indah Selly (Diponegoro University, 2019)
This article aims to describe the structure and meaning of zenbu, subete, and minna adverbials. It also describes the similarities and differences between the three adverbials. Data were obtained from sentences contained in the Kagero Daze Anthology comic and Japanese online articles. Data are classified according to structure and meaning. The structure includes adverbial composition following verbs, nouns and adjectives. To find the similarities and differences of the three adverbial substitution techniques are used. The analysis shows that zenbu, subete, and minna adverbial can follow verbs, nouns, and adjectives. Zenbu has a meaning that states all concrete objects and conditions, subete means all things, everything, for concrete and abstract objects, and states a state, states an idea or thought. Minna has all the meanings for concrete things, things or circumstances, and states people or living things.